Necesidad de Implementar los Inhibidores de Señales de Telefonía Celular en los Centros de Rehabilitación Social - Lozano Luna, Bryam Eduardo (2024)
This curriculum integration paper examines the imperative need to implement cell phone signal jammers in social rehabilitation centers as a measure to address various issues related to the security, management and effective reintegration of inmates. Through a comprehensive review of existing research, the challenges associated with unregulated cell phone use within correctional facilities are identified, including increased violence, coordination of criminal activities, and lack of control over communication by inmates, highlighting growing evidence that unregulated access to mobile devices by inmates has exacerbated security challenges within correctional facilities. From the coordination of criminal activities to intimidation and extortion, the misuse of cell phones represents a significant threat to order and security both inside and outside social rehabilitation centers. The legal and ethical aspects of the implementation of signal jammers are examined, considering both international regulations and national regulations related to human rights, privacy and communication. It also analyzes the potential impact of these measures on the social reintegration of inmates and explores the potential impact of these measures on the social reintegration of inmates. In this context, the implementation of cell phone signal jammers emerges as an effective preventive measure to address the problem of unauthorized use of mobile devices in social rehabilitation centers. These devices, designed to block cell phone signals within a specific area, can help mitigate the risks associated with unregulated inmate communication. However, the implementation of signal jammers poses a number of legal, ethical and practical challenges that must be carefully addressed. It is crucial to ensure that these measures are proportional, necessary and respectful of inmates' fundamental rights. In addition, the technical and logistical implications of implementing signal jammers, as well as their potential impact on legitimate communication by correctional officers and support staff, must be considered.